Construction innovation - Ørstavik, Finn; Dainty, Andrew; Abbott, Carl (Chichester, West Sussex, United Kingdom : Wiley-Blackwell, 2015)
Construction innovation is an important but contested concept, both in industry practice and academic reflection and research. A fundamental reason for this is the nature of the construction industry itself: the industry and the value creation activities taking place there are multi-disciplinary, heterogeneous, distributed and often fragmented. This book takes a new approach to construction innovation, revealing different perspectives, set in a broader context. It coalesces multiple theoretical and practice-based views in order to stimulate reflection and to prepare the ground for further synthesis. By being clear, cogent and unambiguous on the most basic definitions, it can mobilise a plurality of perspectives on innovation to promote fresh thinking on how it can be studied, enabled, measured, and propagated across the industry. This book does not gloss over the real-life complexity of construction innovation. Instead, its authors look explicitly at the challenges that conceptual issues entail and by making their own position clear, they open up fresh intellectual space for reflection. Construction Innovation examines innovation from different positions and through different conceptual lenses to reveal the richness that the theoretical perspectives offer to our understanding of the way that the construction sector actors innovate at both project and organizational levels. The editors have brought together here leading scholars to deconstruct the concept of innovation and to discuss the merits of different perspectives, their commonalities and their diversity. The result is an invaluable sourcebook for those studying and leading innovation in the design, the building and the maintenance of our built environment.
Incentives for innovation in construction -- Built-in innovation and the ambiguity of designing accessibility -- Stakeholder integration champions and innovation in the built environment -- Grassroots innovation in the construction industry -- Stakeholder integration champions and innovation in the built environment -- An industrial network perspective on innovation in construction -- Innovation diffusion across firms -- Clients shaping construction innovation -- Innovation in road building : removing obstacles for diffusion of novel building products -- Innovating for integration : clients as drivers of industry improvement -- Project delivery systems and innovation : the case of us road building -- The leitmotif of building-products innovation in Finland : from commercial technology exploitation to sustainable development.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Civil engineering -- Technological innovations; Construction industry -- Technological innovations; TECHNOLOGY & ENGINEERING -- Civil -- General; Civil engineering -- Technological innovations; Construction industry -- Technological innovations; Electronic books